Parental Involvement in Reading Literacy Program in Developing Students' Religious Character at SD Emirattes Islamic School Jakarta - Nida, Farhah; Rena, Syahidah; Pahrurroji, Pahrurroji (Lembaga Yasin AlSys, 2025)
Literacy and character are essential issues in the national education evaluation system. Literacy is related to the ability to analyze qualitatively. Meanwhile, the character is a bond that helps students become good individuals. Therefore, this research aims to explore the effectiveness of parental involvement in the reading literacy program in developing students' religious character at SD (Elementary School) Emirates Islamic School in Jakarta. The researchers used a qualitative method with data collection through observation, interviews, and documentation. The researchers' data analysis underwent three stages: data reduction, presentation, and conclusion. The research results indicate parental involvement in the reading literacy program's effectiveness in developing students' religious character, such as modelling, mentoring, and organizing. The description of students' religious character in their daily lives is the belief in carrying out the pillars of Islam, their obligations in worship, students involving Allah SWT in their daily lives, and students sharing. It means that the formation of students' character will be achieved if parents can carry out their duties and roles well, especially in strengthening reading literacy at home.